Molecular Docking Study of Ferulic Acid Analog Compounds as Lung Antifibrotic at TGF-β1 Receptors - Pebrianti, Denayu; Ekowati, Juni; Ainurrizma, Dhea Ananda (Universitas Airlangga, 2023)
Pulmonary fibrosis was one of the conditions that occurred in Post-COVID Syndrome patients. Development of specific treatment as an agent to treat pulmonary fibrosis was still ongoing. Ferulic acid was a compound that had a potential lung antifibrotic agent through the inhibition of TGF-β1-mediated signaling. Molecular docking studies using the AutoDock Tools program version 1.5.7 were conducted on ferulic acid and its analogs to determine the activity of compounds as antifibrotic. Furthermore, the interaction of the compounds with the receptor was visualized using the Discovery Studio 2021 program. The results showed that ferulic acid and its analogs had lower free energy than Pirfenidone, which was a standard lung antifibrotic drug. 4-Benzoyloxy-3-methoxycinnamic acid was the compound that had the greatest activity. The group that contributed to the ligand-receptor interaction was the aromatic group with π interaction. Keywords: Molecular Docking, AutoDock, Antifibrotic, TGF-β1, Ferulic Acid